2015
DOI: 10.1017/s1751731115001093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in ovo injection of bovine lactoferrin before incubation in layer breeder eggs on tibia measurements and performance of laying hens

Abstract: There is increasing concern about welfare of laying hens in cages, and one aspect of this topic relates to bone fragility. Therefore, bone anabolic components such as bovine lactoferrin (bLF) may be an effective strategy to maintain the integrity and health of bones. A total of 1080 eggs were divided into four groups with three replicates, each comprising 270 eggs; (1) control group was injected with 100 μl of normal saline per egg; (2, 3 and 4) groups including 22.5 (low), 45 (medium) and 67.5 µg (high) of bL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In this regard, researchers have demonstrated that thermal manipulation during embryogenesis regulated chick weight while exerting long-lasting effects on posthatch thermoregulation and stress response ( Goel et al, 2022 , 2023 ). Similarly, Saki and Mahmoudi (2015) demonstrated that in ovo injections of bovine lactoferrin in layer eggs resulted in increased egg weight and improved tibial strength in 28-wk-old laying hens. Along these lines, promoting embryonic development and subsequent pullet growth via sustained probiotic supplementation could serve as a potential means to improve production and health status of laying hens.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In this regard, researchers have demonstrated that thermal manipulation during embryogenesis regulated chick weight while exerting long-lasting effects on posthatch thermoregulation and stress response ( Goel et al, 2022 , 2023 ). Similarly, Saki and Mahmoudi (2015) demonstrated that in ovo injections of bovine lactoferrin in layer eggs resulted in increased egg weight and improved tibial strength in 28-wk-old laying hens. Along these lines, promoting embryonic development and subsequent pullet growth via sustained probiotic supplementation could serve as a potential means to improve production and health status of laying hens.…”
Section: Resultsmentioning
confidence: 92%
“…However, one of the critical periods of development that influences health and performance in poultry is the embryonic and posthatch phase (d 1 to sexual maturity; Nahashon et al, 1994 ). Furthermore, studies have shown that major diseases of later life originate from impaired embryonic growth and development ( Godfrey and Barker, 2000 ; Saki and Mahmoudi, 2015 ). Consequently, an approach that supports growth and development during these early stages is expected to have a significant effect on overall health and performance of laying hens ( Foye et al, 2007 ; Hulet et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, bone fragility is a significant issue for laying hens kept in cages; therefore, lactoferrin, one of the bone anabolic components, was successful in increasing the strength and weight of tibia bones as well as the weight of eggs in laying hens by injecting lactoferrin into their eggs at a rate of 67.5 g per egg [ 78 ]. In the Humphrey et al [ 79 ] study, chicks were given rice that had been genetically modified to express human lysozyme and lactoferrin with a total amount of transgenic plus conventional rice of 20% in corn soya-based ration to evaluate the impact on growth performance and intestinal health.…”
Section: Introductionmentioning
confidence: 99%